Imagem e escrita: o livro didático de História para o ensino médio sob o Programa Nacional do Livro Didático (PNLD) - Bandouk, Gabriel Luiz (2014)
This work analyzes the pictures and the writing in high school History books in accordance with Programa Nacional do Livro Didático (National Textbook Program) PNLD, created by the federal government in 1985. The data from this survey, organized in graphs and tables, identified permanence and changes in the pictures and in the writing of high school History books through a comparative table of the two most sold books to PNLD with four other previous collections published by major publishers, two of them published between 1980 and 1990, when PNLD did not cover History in High School and two other editions published between 1960 and 1970, thus preceding PNLD. Initially we recovered the history of PNLD when it was observed that this program has helped to increase the number of teaching collections and to bring major foreign publishers to Brazil, as the purchase of millions of books which were given for free to all public schools in the country, was guaranteed by the government. This new reality has helped to promote a more careful publishing of textbooks since Basic Education Department, in partnership with federal universities assumed the responsibility to coordinate and evaluate the competing works. Although it was created in 1985, it was only in 2005 that PNLD contemplated History and so far two high school PNLDs were conducted related to it, the first one was between 2007 and 2008 and the other between 2011 and 2012.